Three years of experience with a novel "virtual" pneumonia follow-up clinic. Issue 3 (10th September 2017) - Wilcox, Christopher R.; Krishnan, Jamie V.; Duffus, Claire; Marshall, Ben G.
Community-acquired pneumonia (CAP) remains the leading cause of adult mortality from infectious disease in the developed world, and carries a huge economic burden [1]. The annual expenditure attributable to CAP is estimated at 10 billion euros and 10 billion dollars for hospitals in Europe and the USA, respectively [2]. Furthermore, older people are disproportionally affected by CAP, and the projected increases in the elderly population over the coming years will put increasing strain on health services [2]. A virtual pneumonia follow-up service provides significant efficiency savings and retains high quality patient care http://ow.ly/AUov30dRIXe